Notes on the species of the genus Hyadina from China (Diptera: Ephydridae) - Zhou, Dan; Zhang, Junhua; Yang, Ding (Zootaxa, 2010)
Two species of Hyadina Haliday, H. pulchella Miyagi and H. guttata (Fallén), are recorded from China for the first time and are redescribed. Their male genitalia are illustrated in detail. The first species, H. pulchella Miyagi occurs in both Oriental and Palaearctic China. The second species, H. guttata (Fallén) is found in Palaearctic China. A key is presented to separate the six known species from China.